2019
DOI: 10.1111/1759-7714.13124
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of RAD51AP1 suppresses epithelial–mesenchymal transition and metastasis in non‐small cell lung cancer

Abstract: Background Non‐small cell lung cancer (NSCLC) is a major cause of cancer‐related mortality and is frequently accompanied by metastasis. The crucial roles of genes in lung cancer have attracted attention. Thus, this study aimed to investigate the effects of RAD51AP1 on the epithelial–mesenchymal transition (EMT) and metastasis of NSCLC. Methods The positive expression rate of the RAD51AP1 protein was examined. NSCLC cells were transfected with a series of plasmids to alter the expression of RAD51AP1 to clarify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
(32 reference statements)
1
19
0
Order By: Relevance
“…Genes dysregulated according to tumour grade included CDC45 and RAD51AP1 , which are both associated with the ALT pathway [ 99 , 100 , 101 ]. They have been linked with increased growth and progression in various cancers, including colorectal, ovarian and lung cancer [ 102 , 103 , 104 ], but have not previously been studied in EC. Between stages I and IV, MAGEA4 and TDRD10 were amongst the most highly upregulated DEGs, and DUT was the most downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Genes dysregulated according to tumour grade included CDC45 and RAD51AP1 , which are both associated with the ALT pathway [ 99 , 100 , 101 ]. They have been linked with increased growth and progression in various cancers, including colorectal, ovarian and lung cancer [ 102 , 103 , 104 ], but have not previously been studied in EC. Between stages I and IV, MAGEA4 and TDRD10 were amongst the most highly upregulated DEGs, and DUT was the most downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…RAD51-associated protein 1 (RAD51AP1) interacts with RAD51, which plays an important role in RAD51-related homologous recombination ( Wang et al, 2019 ). A recent study found that RAD51AP1 is highly expressed in non-small cell lung cancer patients and facilitates invasion and metastasis by inducing epithelial-mesenchymal transitions ( Wu et al, 2019 ). ISG15 is related to chemosensitivity in pancreatic cancer ( Ina et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…RAD51AP1 regulates DNA repair processes as a critical part of RAD51-mediated homologous recombination, which suggests that RAD51AP1 is particularly relevant in cancer. Research has shown that overexpression of RAD51AP1 is found in many cancers, such as human non-small cell lung cancer (NSCLC), ovarian cancer, and breast cancer [10][11][12][13]. Down-regulating RAD51AP1 not only inhibits epithelial-mesenchymal transformation and metastasis of NSCLC in vivo but also reduces the proliferation of ovarian and lung cancer cells in vitro [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that overexpression of RAD51AP1 is found in many cancers, such as human non-small cell lung cancer (NSCLC), ovarian cancer, and breast cancer [10][11][12][13]. Down-regulating RAD51AP1 not only inhibits epithelial-mesenchymal transformation and metastasis of NSCLC in vivo but also reduces the proliferation of ovarian and lung cancer cells in vitro [11,12]. A high RAD51AP1 expression level has been detected in the blood of patients with ovarian cancer and in human breast tumor tissue, and patients with overexpression of RAD51AP1 have inferior overall survival [12,13].…”
Section: Discussionmentioning
confidence: 99%